Kepemimpinan Karismatik, Keadilan Organisasi, dan Kecerdasan Emosional terhadap OCB Karyawan Milenial Perbankan: Peran Mediasi Komitmen Afektif - Ridwansyah (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the influence of charismatic leadership, organizational justice, and emotional intelligence on organizational citizenship behavior (OCB) among millennial employees in the banking sector, with affective commitment as a mediating variable. The research was conducted in Pontianak City, involving 250 banking employees aged 28–43 years who had worked for at least one year. Data were collected using a structured questionnaire with a five-point Likert scale, while the analysis was carried out through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that charismatic leadership, organizational justice, and emotional intelligence positively and significantly affect OCB, both directly and indirectly through affective commitment. These findings support previous studies emphasizing the role of leadership, fairness, and emotional intelligence in fostering extra-role behavior. Theoretically, this research contributes to the literature by integrating three key antecedents within the framework of social exchange theory. Practically, the results recommend that banks develop charismatic leadership training, implement transparent justice systems, and provide emotional intelligence development programs to strengthen the affective commitment of millennial employees. Such efforts are expected to reduce turnover intention and encourage OCB, thereby supporting the sustainable competitiveness of the Indonesian banking sector.